2017
DOI: 10.1007/s13202-017-0395-2
|View full text |Cite
|
Sign up to set email alerts
|

The oil and gas industry must break the paradigm of the current exploration model

Abstract: An analysis of the exploration model that the oil and gas industry currently follows suggests that it often restricts innovation and inhibits exploration efforts. Examples of large, underexplored areas with significant oil and gas potential demonstrate how the current exploration model fails to allow adequate exploration efforts to be conducted. A description of a possible new exploration model is presented, involving the use of exploration technologies already available, as a means of breaking the paradigm of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…The challenges of acquiring, transmitting, storing, and processing seismic data are non-trivial. The seismic methods used extensively in the oil and gas industry are costly and time consuming; seismic surveys require operators to assume substantial cost and risk [ 44 ]. Likewise, seismic methods employed within the scientific community are typically costly and time consuming.…”
Section: Motivationmentioning
confidence: 99%
“…The challenges of acquiring, transmitting, storing, and processing seismic data are non-trivial. The seismic methods used extensively in the oil and gas industry are costly and time consuming; seismic surveys require operators to assume substantial cost and risk [ 44 ]. Likewise, seismic methods employed within the scientific community are typically costly and time consuming.…”
Section: Motivationmentioning
confidence: 99%
“…La mayoría de los estudios geofísicos realizados en la industria petrolera tiene un interés en la profundidad de investigación inferior a 1 km. (Bruckshaw, 1941;Jones, 2018). Por otra parte, la geofísica aplicada a la investigación hidrogeológica para determinar los recursos de agua subterránea y su conectividad, generalmente tienen interés a una profundidad no mayor a 250 m (Kelly y Mares, 1993;Sánchez-Higueredo et al, 2020;Senos Matias, Marques da Silva, Ferreira y Ramalho, 1994).…”
Section: Aplicaciones Y Profundidad En La Investigación Agrícola Y Forestalunclassified
“…Sustainability in procurement is thus, hampered by the high cost of acquiring capital goods and other important infrastructural development that must be implemented to replace current production systems with sustainable, state-of-the-art systems. Jones (2018) suggested that most production systems used by oil-producing companies were acquired many years ago, with some being obsolete. It can further be argued that many oil-producing companies have not adopted the concept of green products because of their prohibitive cost.…”
Section: Leadership In Change Managementmentioning
confidence: 99%